SOFT SKILLS FOR THE SUCCESS OF INTERNATIONAL COLLABORATIVE PROJECTS: AN EMPIRICAL STUDY: Received: 12th October 2023; Revised: 18th October 2023, 26th October 2023; Accepted: 31st October 2023 - Châteaureynaud, Marie-Anne; Dr. Marie-Christine Deyrich; Dr. Marie-France Burgain (PUPIL: International Journal of Teaching, Education and Learning, 2023)
Research collaboration is expected to offer many advantages, including the pooling of ideas, the creation of a shared identity and efficiency in the production of resources. This viewpoint has led to the development of a Europe-wide project involving several partner universities over 9 years. Many researchers are joining forces to work on collaborative projects, in the hope of benefitting science and the common good. However, these projects can be hampered by a number of difficulties, including too little recognition of the importance of cross-disciplinary skills in bringing a group project to a successful conclusion. Our presentation will review the specific features of the collaborative research context and focus on the specific cross-disciplinary skills required with the objective to successfully complete collaborative research projects. Our methodology based on qualitative research will show our experience of several international collaborative projects, which we will supplement with a corpus of exchanges and interviews. Our findings from this project show that among the causes of the difficulties encountered, those relating to cross-disciplinary skills are central and among the skills required for collaborative research projects to run smoothly, our results highlight some of them. Our research shows the importance of the social link and soft skills in collaborative research projects and could be useful in future to those who want to start a new project and who may have underestimated the central importance of these soft skills.